Laser annealing in Si and Ge: Anomalous physical aspects and modeling approaches. (May 2017) - Lombardo, S.F.; Boninelli, S.; Cristiano, F.; Fisicaro, G.; Fortunato, G.; Grimaldi, M.G.; Impellizzeri, G.; Italia, M.; Marino, A.; Milazzo, R.; Napolitani, E.; Privitera, V.; et al.
Abstract: Laser annealing of semiconductor materials is a processing technique offering interesting application features when intense, transient and localized heat sources are needed for electronic device manufacturing or other nano-technological applications. The space-time localization of the induced thermal field (in the nanoseconds/nanometers scale) promotes interesting non-equilibrium phenomena in the processed material which only recently have been systematically investigated and modelled. In this review paper we discuss the current knowledge on anomalous kinetics occurring in implanted silicon and germanium (i.e. thin layers of disorder diluted alloys of Si and Ge, with variable initial disorder status according to the implantation conditions) during the pulsed laser irradiation. In particular, we focus our attention on the anomalous impurity redistribution in the transient melting stage and on the formation of non conventional and metastable extended defects.